2010
DOI: 10.1007/s11274-010-0406-7
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota of the Planalto de Bolona: an artisanal cheese produced in uncommon environmental conditions in the Cape Verde Islands

Abstract: The present study aimed to evaluate the dominant microbial community naturally present in the Planalto de Bolona cheese, produced in the Cape Verde Islands. Samples of milk, curd and cheese from two different producers were examined through culture-dependent and independent-methods. Traditional plating and genetic identification of lactic acid bacteria (LAB) and yeast isolates were carried out. Moreover, DNA and RNA extracted directly from samples were subjected to Polymerase Chain Reaction-Denaturing Gradient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 33 publications
0
17
0
2
Order By: Relevance
“…At each sampling point, 1 ml of the first 10-fold serial dilution was collected and directly centrifuged at maximum speed for 30 s. Nucleic acid was extracted from two of three biological replicates from each batch. Total DNA was extracted as described by Alessandria et al (20). DNA was quantified using a NanoDrop 1000 spectrophotometer (Thermo Scientific, Milan, Italy) and standardized at 100 ng/l.…”
Section: Preparation Of Antimicrobial Bags and Filmsmentioning
confidence: 99%
“…At each sampling point, 1 ml of the first 10-fold serial dilution was collected and directly centrifuged at maximum speed for 30 s. Nucleic acid was extracted from two of three biological replicates from each batch. Total DNA was extracted as described by Alessandria et al (20). DNA was quantified using a NanoDrop 1000 spectrophotometer (Thermo Scientific, Milan, Italy) and standardized at 100 ng/l.…”
Section: Preparation Of Antimicrobial Bags and Filmsmentioning
confidence: 99%
“…Several researches suggested that the NSLAB can contribute to the typical or atypical but desirable fl avour development and to the organoleptic properties of particular cheeses. The NSLAB can also be responsible for off fl avour development and overproduction of CO 2 [Mounier et al, 2008]. In some cheeses, yeasts can cause defects such as excessive gas production, bitter taste, fruit fl avours, increased acidity and changes in texture profi le [Wyder, 2001;Bockelmann, 2010].…”
Section: Introductionmentioning
confidence: 99%
“…QPCR 142 amplifications, targeting the V3 region of the 16S rRNA gene, were performed in a final volume of 25 µl, 143 using SSo Advanced Sybr Green Supermix (Bio-Rad, Italy). One µl of cDNA was amplified with 338f 144 and 518r primers at a final concentration of 400 nM in a Chromo 4 real-time PCR Detection System 145 (Biorad, Milan, Italy) (Alessandria et al, 2010). In all cases and at each step the bacterial 146 counts was checked by triple plate counting routine methods and Standard curves were constructed by 147 plotting the threshold cycle (C T ) values against log CFU/g or CFU/ml on MRS agar.…”
mentioning
confidence: 99%